Occurrence of toxigenic Aspergillus flavus in commercial Bulgur wheat - FARIA,Carla Bertechini (2017)
Abstract Aflatoxins are mutagenic, carcinogenic, and teratogenic mycotoxins. The objective of this work was to study the presence of aflatoxigenic Aspergillus in commercial Bulgur wheat in the city of Maringá, Paraná, Brazil. Thirty samples of commercial Bulgur wheat, acquired in the period of August 2011 to January 2012, were evaluated. The enumeration analysis showed that samples had up to 273.3 CFU of molds and 133.3 CFU of aflatoxigenic Aspergillus per gram of wheat. Forty-two monosporic isolates were obtained and identified as Aspergillus flavus. The isolates were analyzed regarding their aflatoxigenic potential by culture in coconut milk agar; hydroxide vapor exposure; chromatography; and polymerase chain reaction (PCR) targeting genes that code enzymes of the aflatoxins synthesis pathway. Some of the isolates were confirmed to be aflatoxin producers and several of them presented a genetic profile of aflatoxin synthesis. The obtained results demonstrated that Bulgur wheat A. flavus contamination is concerning.